The Managing of Sport Center: A Case Study - Arijana Llagjevic-Govori; Enver Tahiraj; Dardan Llagjaj (Indonesian Journal of Sport Management, 2022)
The sport centre in Prishtina as a public property has the role of functioning the sportsmen services and their clubs doing the sport and competitive activities. Sport Centre “Pallati I Rinisë” (Youth Palace) in Prishtina, as a complex includes the manifestation of different kinds of activities: social, public, cultural, entertaining, sport-recreation, economic activities, the centre that has began its function around 1977 with the total operating space of 8.136 m2. The goal in this project is the managing of this object, into which there are two sport halls ;the big and the small one, with about 1.450 m2 (the small hall) and 5 mini halls of about 1.130m2 for different sport trainings, also it is included national medical centre of sport with an area of 480m2. In this project is used the SWOT analyze dedicated for in this centre for sportsmen and competitors of different sports per m2. In this written work, prospective steps of developing of this centre have been treated, then more sports spaces will be created for sportspersons and their compete activities for the specific sport.